The Sardar sub-equation technique for obtaining some optical solitons of cubic nonlinear Schrödinger equation involving beta derivatives with Kerr law nonlinearity - Altwaty , Abdulmalik A.; Amhalhil , Jaffalah J.; El Sakori, Ahmed; Meriki, Ngla F. (Scientific Journal of University of Benghazi, 2024)
This study investigates new optical and chirped optical solitons for the space-time fractional cubic nonlinear Schrödinger equation using the Sardar sub-equation technique in the presence of Kerr law nonlinearity. The solutions are expressed in terms of hyperbolic and trigonometric functions, revealing a diverse range of behaviors within the system. The identified optical and chirped optical soliton types include dark, bright, kink, and periodic, showcasing a rich spectrum of phenomena. Representing soliton solutions using 2D and 3D graphs with varying parameters leads to a better understanding of their formation and characteristics. The findings contribute to the comprehension of nonlinear dynamics, offering insights into phenomena relevant to nonlinear optics, quantum mechanics, and condensed matter physics.